Density functional theory-based study of the magnetic and optical properties of PbMO3 (M = Cr, Fe) using the modified BeckeJohnson mBJ functional - Mahmood, Q.; Hassan, M.; Bhamu, K.C.; Yaseen, M.; Ramay, S.M.; Mahmood, A. (Journal of Physics and Chemistry of Solids, 2019)
In this study, we employed the density functional theory (DFT) approach using WIEN2k code to study the magnetic and optical behaviors of PbCrO3 and PbFeO3 perovskites in both cubic and tetragonal phases. We determined the stability of the ferromagnetic state in terms of the enthalpy of formation, the half-metallic behavior, and spin polarization. The origin and nature of the ferromagnetic state were attributed to John-Teller distortion and a super-exchange mechanism. Comparisons of the calculated crystal field, John-Teller distortion, and exchange energies indicated the stability of the ferromagnetic nature. Due to strong hybridization, the magnetic moment was reduced at the Cr/Fe sites but generated at the nonmagnetic sites. The optical characteristics were explained by in-depth analyses of the polarization, plasmonic resonance, transparency, and other features in terms of the computed parameters.

Density functional theory-based study of the magnetic and optical properties of PbMO3 (M = Cr, Fe) using the modified BeckeJohnson mBJ functional (vol 128, pg 275, 2019) - Mahmood, Q.; Hassan, M.; Bhamu, K. C.; Yaseen, M.; Ramay, S. M.; Mahmood, A. (Journal of Physics and Chemistry of Solids, 2021)